Biological longitudinal aspects of the Kabompo River, a significant tributary of the upper Zambezi sub-catchment, North-west Province, Zambia - Janse van Rensburg, Lomarie Cathleen (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The landscape of the Upper Zambezi Catchment in the remote North-Western Province of Zambia retains many natural features, but current and future anthropogenic activities threaten its integrity. Lack of information relating to the basic ecological functioning of the region hampers conservation efforts. Flooding from the adjacent woody-savanna and open grasslands in the Upper-Zambezi Catchment in the wet season drives crucial processes in the aquatic ecosystems such as the Kabompo River. This thesis describes aquatic food webs and describes the nutrient cycling in this river. A general introduction was based on the seasonality, river morphology, and biodiversity of the Kabompo River. There is no aquatic food web information available on this river. To address this knowledge gap, sampling of the principal food web components"“ vegetation, invertebrates, and fish "“ were collected in the dry season from August to September 2019 across six sites in the Kabompo River. Stable isotope analyses provided proxies for the food web structure at each site, and were the basis of longitudinal comparisons. The analyses suggest that the Kabompo River food webs follow the trophic ordination and nutrient cycling characteristic of the revised-Riverine Productivity Model. Food webs and community assemblages remain structurally similar between sites and provide some evidence of bottom-up productivity-driven trophic dynamics. To predict the possible landscape-scale processing of nutrient changes present for the aquatic ecosystems of the Kabompo River, a longitudinal comparison between a herbivore, Labeo cylindricus, and omnivore, Synodontis spp., fish species and their resources (primary producers and invertebrates) was done and showed archetypal fish food web trophic separation (2 "° to3 "°) between species which remains consistent for the headwater sites. The nutrient values change at the convergence between the Kabompo Bridge and the Mwinilunga branches and show a decrease in the trophic separation of the sites below. This change becomes apparent from the last site, Watopa, where the trophic separation re-establishes (2 "° to 3 "°) between the species. The trend suggests primarily autochthonous production in the headwater reaches, changing to allochthonous and autochthonous nutrient incorporation after the convergence of the two main branches. Permanent wetlands surrounding the convergence zones may be conducive to more primary producer activity and increased nutrient turnover. Permanent wetlands are a common feature of the Upper Zambezi Catchment tributaries, with the most notable lentic system the Barotse Flood Plains in the south, which shares reach-adjacent characteristics with the Kabompo River. Trends from the 2015 dry season identified for the Barotse Flood Plains support the findings of this thesis, where the Î´13C values recorded reach depletion of -45 "°. Management in the Upper Zambezi Basin and the Kabompo River comprises biannual assessments of water quality and quantity by the Zambezi River Authority, but not of the ecosystem process. This thesis may provide information to address the ecological (food webs and nutrient cycling) dynamics of the Basin rivers. As the first baseline information on the river's biology and ecology, it may present a comparative basis for future assessments under conservation management strategies.
Keywords: Nutrient cycles; Stable isotopes; Redeye Labeo; Synodontis; Zambezi River Watershed -- Ecology; Aquatic ecology